Polysaccharide of Atractylodes macrocephala Koidz (PAMK) Alleviates Cyclophosphamide-induced Immunosuppression in Mice by Upregulating CD28/IP3R/PLCγ-1/AP-1/NFAT Signal Pathway - Xiang, Xuelian; Cao, Nan; Chen, Feiyue; Qian, Long; Wang, Yifei; Huang, Yunmao; Tian, Yunbo; Xu, Danning; Li, Wanyan (Frontiers in Pharmacology, 2020)
The polysaccharide of Atractylodes macrocephala Koidz (PAMK) is recognized as an immune enhancer, with anti-cancer, anti-tumour, lymphocyte-activating and lymphocytes proliferation-inducing effects. For investigating the mechanism that PAMK alleviates the decline in T cell activation induced by CTX, 24 6-week-old BALB/c female mice were randomly divided into four groups (C, PAMK, CTX, PAMK + CTX). The spleen index, splenocytes morphology and death, cytokine concentration, T cell activating factors (CD25, CD69, CD71), mRNA expression levels related to the CD28 signal pathway were detected. Furthermore, the lymphocytes of mice was isolated and cultured, and then the Th1/Th2 ratio, activating factors, mRNA levels related to the CD28 signal pathway were detected. The results showed that PAMK significantly improved the spleen index, alleviated abnormal splenocytes morphology and death, maintained the balance of Th1/Th2 cells, increased the levels of IL-2, IL-6, TNF-α, and IFN-γ, and increased the mRNA levels of CD28, PLCγ-1, IP3R, NFAT, and AP-1. In conclusion, PAMK increased cytokines levels and alleviated the decline in activation level of lymphocytes induced by CTX through CD28/IP3R/PLCγ-1/AP-1/NFAT signal pathway.